Putting Victims First: Confronting Challenges in India's Criminal Justice System - Bhattacharjee, Anuleena; Basu, Ritu (International Journal of Psychosocial Rehabilitation, 2020)
The paper explores the intricacies of India's criminal justice system, with a specific emphasis on the often-overlooked rights and requirements of victims. The paper assesses the current landscape in India, critically evaluating the involvement of victims at various stages of India's criminal justice system, such as pre-trial processes, victim involvement during trials, and the compounding and withdrawal of cases, and delves into the post-trial support for victims. Highlighting the limited and passive role victims currently play in these processes and contrasting this with more victim-centered approaches in France and the United States, the authors aim to offer constructive recommendations for enhancing victim justice in India.